Duration of antibiotic treatment after endoscopic ultrasound‐guided drainage of walled‐off pancreatic necrosis not affecting outcomes. Issue 8 (25th March 2018) - Sahar, Nadav; Kozarek, Richard A; Kanji, Zaheer S; Chihara, Shingo; Gan, Seng Ian; Gluck, Michael; Larsen, Michael; Ross, Andrew S; Irani, Shayan
Abstract: Background and Aim: Although society guidelines recommend a short course of antibiotics after drainage of walled‐off necrosis (WON), the exact duration is unclear. Methods: This is a retrospective review of patients with no prior antibiotic exposure who underwent dual‐modality drainage (DMD) for sterile WON from 2008 to 2017. Patients were grouped into short duration (SD, ≤5 days) versus long duration (LD, >5 days). The main outcome was the frequency of recurrent infections. Results: Sixty‐one patients (25 in the SD group and 36 in the LD group) were included. Patients in the two groups had comparable age, comorbidities, and severity of disease ( P = 0.89). Patients in the SD group were treated with antibiotics for a median of 3 days compared with 8.5 days in the LD group. There were no differences in recurrent febrile episodes within 30 days of procedure—44% of SD group versus 39% of LD ( P = 0.69). There was also no difference in time to resolution of WON (64 days for both groups, P = 0.72) or duration of hospitalization post‐DMD (SD 7.7 days versus LD 7.5 days, P = 0.42). Three cases of Clostridium difficile colitis were observed in the LD group. Conclusions: Longer course of antibiotics seems to have similar outcomes compared with shorter courses in patients with WON treated with DMD. Prolonged‐course therapy may predispose to secondary infections like C. difficile colitis. A randomized controlled trial is needed to evaluate the role and duration of peri‐procedural antibiotics after drainage of sterile WON.